Financial debt and family bankruptcy: the Peruvian case - Narváez Liceras, Alejandro (2020)
As of the second half of 2020, the total number of financial debtors (individuals) by type of credit (consumer and mortgage) amounted to 7,310,779. There are millions of families with financial difficulties to honor their commitments with lenders (banks, savings banks, finance companies, edpymes, etc.) as a result of the coronavirus. In the current scenario of exceptional health, economic and financial crisis, a debt reduction or reduction can avoid the non-payment of said debts and the bankruptcy of families. The main objective of this research work is to demonstrate that the entities of the Peruvian financial system have a solid financial solvency, to release part of the debt to their borrowers without compromising their stability. Two conclusions of the study: a) the impact of the removal of part of the debts receivable is minimal in the total income of financial institutions, and b) the solutions proposed by Congress and banks (reschedule, refinance or freeze debts) do not solve the underlying problem, but on the contrary, debts will become unpayable with the accumulation of interest.